Arab Media Systems - Richter, Carola; Kozman, Claudia (Global Communications, 2021)
"This volume provides a comparative analysis of media systems in the Arab world, based on criteria informed by the historical, political, social, and economic factors influencing a country's media. Reaching beyond classical western media system typologies, Arab Media Systems brings together contributions from experts in the field of media in the Middle East and North Africa (MENA) to provide valuable insights into the heterogeneity of this region's media systems. It focuses on trends in government stances towards media, media ownership models, technological innovation, and the role of transnational mobility in shaping media structure and practices. Each chapter in the volume traces a specific country's media - from Lebanon to Morocco - and assesses its media system in terms of historical roots, political and legal frameworks, media economy and ownership patterns, technology and infrastructure, and social factors (including diversity and equality in gender, age, ethnicities, religions, and languages). This book is a welcome contribution to the field of media studies, constituting the only edited collection in recent years to provide a comprehensive and systematic overview of Arab media systems. As such, it will be of great use to students and scholars in media, journalism and communication studies, as well as political scientists, sociologists, and anthropologists with an interest in the MENA region. "